Melatonin-Eluting Contact Lenses Effect on Tear Volume: In Vitro and In Vivo Experiments - María Serramito; Ana F. Pereira-; Carlos Carpena-Torres; Fernando Huete-Toral; Carmen Alvarez-Lorenzo; Gonzalo Carracedo (MDPI AG, 2022)
(1) Background: The purpose of this study was to synthesize melatonin-eluting contact lenses (CLs) and evaluate both the ocular kinetics of the released melatonin and its effect on tear volume and intraocular pressure. (2) Methods: In vitro, melatonin-eluting CLs were synthesized by using non-functionalized (HEMA) and functionalized (HEMA/APMA) monomers. In vivo, a short-term prospective and randomized study was performed on 15 rabbits divided into two groups: 12 rabbits wearing functionalized CLs and 3 rabbits without CLs as a control. The melatonin levels in tears, aqueous humor, vitreous body and retina, tear volume, and intraocular pressure were measured for 8 h. (3) Results: In vitro, both monomers did not show differences in terms of melatonin loading and release (p ≥ 0.05). In vivo, the melatonin concentration was elevated in tears and aqueous humor after 2 and 4 h of wearing CLs, respectively (p < 0.05). Additionally, the CLs increased tear volume for 2 h (p < 0.05). (4) Conclusions: The melatonin-eluting CLs released their content over the ocular surface for at least 2 h, which was associated with a secretagogue effect on tear volume. However, the increased amount of melatonin found in the aqueous humor had no effect on intraocular pressure.